Effects of different brewing techniques on the contents of acetoin and ligustrazine in Shanxi aged vinegar - LANG Fanfan, XIA Yaoyao, SHEN Jin, LIANG Yanwen, ZAN Xuemei, YAN Yufeng (Zhongguo niangzao, 2024)
In order to improve the production process and enhance the quality of aged vinegar, using Cupei as the research object, the changes in alcohol content, total acid, acetoin and ligustrazine were examined during traditional and mechanical acetic acid fermentation processes, and the effects of traditional and mechanical fumigation methods on acetoin and ligustrazine contents were studied. The results showed that under the traditional acetic acid fermentation process, the alcohol content, total acid, acetoin and ligustrazine contents in the Cupei were 0.37%vol, 4.85 g/100 ml, 706.67 mg/L and 0.38 mg/L at the end of fermentation, respectively. Under the mechanical acetic acid fermentation process, the alcohol content, total acid, acetoin and ligustrazine contents were 0.75%vol, 4.25 g/100 ml, 2 933.33 mg/L and 1.33 mg/L at the end of fermentation, respectively. Under the traditional acetic acid fermentation process, the contents of acetoin and ligustrazine in the Cupei with traditional and mechanical fumigation process were 200.23 mg/L, 3.15 mg/L, and 10.45 mg/L, 11.18 mg/L at the end of fermentation, respectively. Under the mechanical acetic acid fermentation process, the acetoin and ligustrazine in the Cupei with traditional and mechanical fumigation process were 1 666.63 mg/L, 4.73 mg/L, and 137 mg/L, 17.63 mg/L at the end of fermentation, respectively. Therefore, mechanical acetic acid fermentation and mechanical fumigation process were selected.